Claire’s Anxiety Disorder and Justine’s Depression After Her Mother’s Frustration in Melancholia - Retno Ramadhina (Jurnal Pengetahuan dan Pendidikan, 2025)
The researchers selected the 2011 film Melancholia, written and directed by Lars von Trier, as the primary source of analysis because it offers significant insights that are relevant to contemporary society, particularly in understanding psychological and social phenomena. The film portrays circumstances and conditions that closely resemble issues experienced in modern life, especially those related to mental health and social instability. This study employs a qualitative research methodology to analyze the data presented in the film. As a science fiction drama, Melancholia provides a symbolic representation of human responses to crisis and existential threat. The researchers apply both sociological and psychological approaches in examining the narrative and characters. The sociological approach utilizes social conflict theory and social chaos theory to interpret the breakdown of social order and interpersonal tensions. Meanwhile, the psychological approach focuses on social rejection, anxiety disorders, and depression as experienced by the main characters. Through these analytical frameworks, it can be concluded that Melancholia (2011) depicts the genuine struggles of two sisters confronting severe mental health challenges with different underlying causes. Ultimately, the film illustrates resilience, emotional complexity, and human vulnerability in facing catastrophic uncertainty